Re-appraisal of topical 1% voriconazole and 5% natamycin in the treatment of fungal keratitis in a randomised trial. Issue 9 (4th March 2015) - Sharma, Savitri; Das, Sujata; Virdi, Ajoy; Fernandes, Merle; Sahu, Srikant K; Kumar Koday, Nagendra; Ali, Md Hasnat; Garg, Prashant; Motukupally, Swapna R
Abstract : Purpose: To compare the efficacy of topical 1% voriconazole vs 5% natamycin for the treatment of fungal keratitis. Methods: In a prospective, double-masked, randomised, controlled, registered clinical trial, 118 patients with fungal keratitis were treated using identical dosage schedule with either voriconazole (58) or natamycin (60) as inpatients for 7 days and followed up weekly. The outcome measures were percentage of patients with healed or resolving ulcer and final visual acuity at last follow-up (primary) and on day 7 (secondary) in each group. Results: More patients (p=0.005) on natamycin (50/56, 89.2%) had healed or resolving ulcer compared with voriconazole (34/51, 66.6%) at last follow-up. The improvement in vision was marginally greater in patients in the natamycin group compared with the voriconazole group at day 7 (p=0.04) and significantly greater at final visit (p=0.01). In univariate analysis, drug, age and mean size of corneal infiltrate and epithelial defect had a significant effect on the final visual outcome. In multivariate analysis, the effect of drug (voriconazole vs natamycin, adjusted coefficient 0.27 (−0.04 to 0.57), p=0.09) was marginal while the effect of age and epithelial defect was significant (p<0.001 for both). In the group treated with natamycin, the final visual acuity was significantly better (p=0.005, Wilcoxon signed-rank test) in patients with Fusarium keratitis but not with Aspergillus keratitis (p=0.714, paired t test). Conclusions: When compared with voriconazole, natamycin was more effective in the treatment of fungal keratitis, especially Fusarium keratitis. Trial registration number: Clinical Trial Registry India (2010/091/003041).